2006
DOI: 10.1021/ar040243m
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Modulated Palladium-Catalyzed Aerobic Alcohol Oxidations

Abstract: The discovery and investigation of ligand-modulated Pd-catalyzed aerobic alcohol oxidations is documented. The project has evolved from a simple empirical discovery that (-)-sparteine, in combination with Pd(II) salts, facilitates the aerobic oxidative kinetic resolution of secondary alcohols to an in-depth physical organic investigation that has provided key insights into how new, more effective catalysts can be designed. Mechanistic investigations, the substrate scope for the catalysts developed, and implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
153
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(159 citation statements)
references
References 44 publications
0
153
0
6
Order By: Relevance
“…Typical alcohol oxidation methods involve stoichiometric amounts of chromium-or manganese-based oxidants that are hazardous materials requiring special disposal procedures. To use environmentally more friendly oxidants, chemists have developed transition metal-catalyzed oxidations of alcohols in the presence of acetone, [1,2] H 2 O 2 , [3] or O 2 [4] as the oxidant. However, most of these catalytic systems rely on precious metals such as Ru, [1] Ir, [2] and Pd.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typical alcohol oxidation methods involve stoichiometric amounts of chromium-or manganese-based oxidants that are hazardous materials requiring special disposal procedures. To use environmentally more friendly oxidants, chemists have developed transition metal-catalyzed oxidations of alcohols in the presence of acetone, [1,2] H 2 O 2 , [3] or O 2 [4] as the oxidant. However, most of these catalytic systems rely on precious metals such as Ru, [1] Ir, [2] and Pd.…”
mentioning
confidence: 99%
“…However, most of these catalytic systems rely on precious metals such as Ru, [1] Ir, [2] and Pd. [4] The development of new catalysts containing abundant and inexpensive metals, particularly those derived from iron, for the oxidation of alcohols is highly desirable. It has been reported that aerobic alcohol oxidation is catalyzed by FeA C H T U N G T R E N N U N G (NO 3 ) 3 / FeBr 3 [5] or FeCl 3 ·6 H 2 O/NaNO 2 /TEMPO, [6] and the catalytic oxidation of secondary alcohols with tBuO 2 H is affected by FeA C H T U N G T R E N N U N G (NO 3 ) 3 ·9 H 2 O/picolinic acid.…”
mentioning
confidence: 99%
“…Many reports suggest the presence of an alkoxide intermediate in the presence of a base 40,41 (scheme 1).…”
Section: Catalytic Tests For 1-phenylethanol Oxidation In the Presencmentioning
confidence: 99%
“…[36] Die Oxidation von Carbinolen ist ein notorisch energiearmer Prozess, allerdings bleiben enantioselektive Reaktionsverläufe schwierig: Ein bemerkenswertes Beispiel ist die Palladium-Spartein-oder Mangan-Salen-katalysierte Oxidation von racemischem 25, die mit hoher Enantioselektivität ablaufen kann. [37] Anzumerken ist, dass die selektive Oxidation dieser Position auch das Ergebnis einer vorausgehenden Koordination der Alkoholfunktion an das Übergangsmetall-zentrum ist. Auf ähnliche Weise können auch freie Elektronenpaare von Stickstoffatomen die Positionsselektivität in C-H-Oxidationen beeinflussen: Die Oxidation von Nicotin (26) zu Cotinin gelingt mit einer Reihe von Reagentien als Ergebnis der Hyperkonjugation der freien Elektronenpaare des Pyrrolidinstickstoffatoms mit der benachbarten C-H-Bindung.…”
Section: Induktive Effekteunclassified